Treatment of 22q11.2 deletion syndrome-associated schizophrenia with comorbid anxiety and panic disorder - Candace B. Borders; Amanda Suzuki; David Safani (Mental Illness)
22q11.2 deletion syndrome (22q11DS) is a risk factor for psychiatric illnesses, including schizophrenia and anxiety. Small studies have shown that several neuroleptic medications are effective in treating psychosis in this population, but are also associated with an increased risk of adverse effects - particularly, seizures. In this case, we discuss a 34-year-old patient presenting with late onset schizophrenia, which ultimately led to her diagnosis of 22q11DS. Subsequent management of the patient’s psychosis with asenapine was complicated by concurrent anxiety and panic disorder; thus, we examine the role of anxiolytic therapy in conjunction with antipsychotics in this patient population.